A Randomized Trial of Telemonitoring and Self-Care Education in Heart Failure Patients Following Home Care Discharge. (October 2013) - Delaney, Colleen; Apostolidis, Beka; Bartos, Susan; Morrison, Heather; Smith, Liane; Fortinsky, Richard
Patients with heart failure (HF) who have been discharged from a home care agency are a particularly vulnerable group at risk for poor outcomes and high rehositalization rates. The primary aim of this experimental study was to determine the efficacy of a telemonitoring and self-care education intervention in reducing hospitalization and improving quality of life and patient's knowledge of HF after home care discharge. Ninety-three participants completed the study. The primary outcome of 90-day post–home care discharge hospitalization was significantly reduced in the intervention group compared to controls (9 vs. 18, p - .046). HF knowledge ( p = .013) and QOL ( p = .004) were significantly increased in intervention group patients in comparison to control group patients' at the study endpoint.